Advantages of Brazilian chaos: the Brazil that Oswald de Andrade discovered in Paris (ARS, 2018)
During the year of 1923, Oswald de Andrade lived in Paris, where he was in touch with different “intellectual environments”, as he called them, acting as a promoter of the artistic and literary renewing movement started in São Paulo by the Semana de Arte Moderna. The experience he had in the French capital enlarged his reflection on the specificity of both Brazilian culture and intellectual life. This process culminated in the Manifesto da Poesia Pau-Brasil, published a few months after his return to Brazil. By means of the analysis of a conference text, together with letters and articles sent from Paris, this article discusses how the visual arts took part on that specific period of Oswald de Andrade’s intellectual career.